Pengaruh Kualitas Pelayanan Dan Lokasi Terhadap Kepuasan Konsumen Pada Rumah Makan Mie Pedes Mampus ( MPM ) Cabang Puri Bintaro Hijau (PBH) Tangerang Selatan - Kharisma Dinda Oktaviana; Cornelia Dumarya Manik (JURNAL ILMIAH EKONOMI DAN MANAJEMEN, 2026)
This study aimed to determine and analyze the effect of Service Quality (X₁) and Location (X₂) on Consumer Satisfaction (Y) at Mie Pedes Mampus (MPM) Restaurant, Puri Bintaro Hijau (PBH) Branch. The study employed a quantitative research method, with data collected through questionnaires distributed to consumers. The sampling technique used was the Rao Purba formula, based on the condition that the total number of consumers was not known with certainty. The Rao Purba formula was applied because the number of visiting consumers was not specifically documented, making it impossible to determine the exact population size. Based on the calculation using the Rao Purba formula, a sample of 97 respondents was obtained. Data analysis was conducted using simple and multiple linear regression, correlation analysis, coefficient of determination, and hypothesis testing through t-tests and F-tests. The results showed that Service Quality had a positive and significant effect on Consumer Satisfaction, with the regression equation Y = 3.876 + 0.512X₁. The correlation coefficient value of 0.847 indicated a very strong relationship, with a coefficient of determination of 0.717, meaning that Service Quality influenced Consumer Satisfaction by 71.7%, while the remaining 28.3% was influenced by other variables. The hypothesis test showed that the calculated t-value was greater than the t-table value (4.073 > 1.986), thus H₀₁ was rejected and Hₐ₁ was accepted. The Location variable also had a positive and significant effect on Consumer Satisfaction, with the regression equation Y = 3.979 + 0.780X₂. The correlation coefficient value of 0.696 indicated a strong relationship, with a coefficient of determination of 0.485, meaning that Location influenced Consumer Satisfaction by 48.5%, while the remaining 51.5% was influenced by other variables. The hypothesis test showed that the calculated t-value was greater than the t-table value (2.584 > 1.986), thus H₀₂ was rejected and Hₐ₂ was accepted. Simultaneously, Service Quality and Location had a positive and significant effect on Consumer Satisfaction, with the regression equation Y = 3.522 + 0.490X₁ + 0.053X₂. The correlation coefficient value of 0.847 indicated a very strong relationship, with a coefficient of determination of 0.718, meaning that both variables influenced Consumer Satisfaction by 71.8%, while the remaining 28.2% was influenced by other variables. The F-test results showed that the calculated F-value was greater than the F-table value (71.967 > 3.090), thus H₀₃ was rejected and Hₐ₃ was accepted.